The Dynamics of Islamic Thought in Responding to Contemporary Challenges - Hicham Diouane; Muhammad K. Ridwan; Muhammad Zawil Kiram; Abdalrahman Abulmajd (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2025)
This study aims to explore the development and transformation of Islamic thought from its classical roots to contemporary expressions, with a focus on how it responds to modern global challenges such as democracy, human rights, gender equality, and environmental issues. The theoretical framework draws upon the works of classical and modern Islamic scholars, including Al-Ghazali, Ibn Rushd, Muhammad Abduh, and Fazlur Rahman, emphasizing the dynamic interplay between wahy (revelation) and aql (reason), as well as the concept of ijtihad (independent reasoning) and contextual interpretation. Using a qualitative, descriptive-analytical method, this study analyzes selected texts and scholarly contributions to trace the historical trajectory and current discourse within Islamic thought. The findings indicate that Islamic thought is not monolithic, but rather evolves in response to historical and social contexts. Contemporary Muslim thinkers increasingly emphasize the need for contextualization, ethical renewal, and reinterpretation of Islamic sources to remain relevant in the face of current challenges. These results highlight that modern Islamic thought holds significant potential to contribute to social justice, inclusive governance, and human development when rooted in both textual integrity and contextual awareness. The implication of this research is the need to revitalize Islamic education and scholarly engagement with a focus on critical, reformist, and ethical approaches. The originality of this study lies in its synthesis of classical and modern perspectives within a unified narrative that frames Islamic thought as a living, adaptable intellectual tradition capable of informing contemporary discourse in meaningful ways.